Parent B2N2‐Perylenes with Different BN Orientations - Zhang, Peng‐Fei; Zeng, Jing‐Cai; Zhuang, Fang‐Dong; Zhao, Ke‐Xiang; Sun, Ze‐Hao; Yao, Ze‐Fan; Lu, Yang; Wang, Xiao‐Ye; Wang, Jie‐Yu; Pei, Jian (Angewandte Chemie International Edition, 2021)
Introducing BN units into polycyclic aromatic hydrocarbons expands the chemical space of conjugated materials with novel properties. However, it is challenging to achieve accurate synthesis of BN‐PAHs with specific BN positions and orientations. Here, three new parent B2N2‐perylenes with different BN orientations are synthesized with BN‐naphthalene as the building block, providing systematic insight into the effects of BN incorporation with different orientations on the structure, (anti)aromaticity, crystal packing and photophysical properties. The intermolecular dipole–dipole interaction shortens the π–π stacking distance. The crystal structure, (anti)aromaticity, and photophysical properties vary with the change of BN orientation. The revealed BN doping effects may provide a guideline for the synthesis of BN‐PAHs with specific stacking structures, and the synthetic strategy employed here can be extended toward the synthesis of larger BN‐embedded PAHs with adjustable BN patterns. A family of parent B2N2‐perylenes with different BN orientations have been synthesized based on the BN‐naphthalene building block. The effects of BN with different orientations on structure, (anti)aromaticity, crystal packing and photophysical properties are systematically investigated. This work provides an efficient synthetic strategy for BN‐PAHs and a deep insight into the structure–property relationship of BN‐PAHs.